2010
DOI: 10.1051/0004-6361/201014748
|View full text |Cite
|
Sign up to set email alerts
|

The dust content of high-zsubmillimeter galaxies revealed byHerschel

Abstract: We use deep observations taken with the Photodetector Array Camera and Spectrometer (PACS), on board the Herschel satellite as part of the PACS evolutionary probe (PEP) guaranteed project along with submm ground-based observations to measure the dust mass of a sample of high-z submillimeter galaxies (SMGs). We investigate their dust content relative to their stellar and gas masses, and compare them with local star-forming galaxies. High-z SMGs are dust rich, i.e. they have higher dust-to-stellar mass ratios co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 54 publications
27
83
0
Order By: Relevance
“…The stellar masses for these galaxies and with the more topheavy IMFs are in good agreement with observations of galaxies at high-z. Santini et al (2010) and Michałowski et al (2010a) shows that, out of a sample of high-z submillimetre galaxies and local ULIRGs, most of these are assembled at stellar masses around 10 11 M and have dust masses of 10 8−10 M .…”
Section: Discussionmentioning
confidence: 99%
“…The stellar masses for these galaxies and with the more topheavy IMFs are in good agreement with observations of galaxies at high-z. Santini et al (2010) and Michałowski et al (2010a) shows that, out of a sample of high-z submillimetre galaxies and local ULIRGs, most of these are assembled at stellar masses around 10 11 M and have dust masses of 10 8−10 M .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been claimed that ULIRGs show systematically lower metallicities than expected from the mass-metallicity relation (Rupke et al 2008;Caputi et al 2008); but this may simply be a consequence of the fact that in these heavily obscured systems the optical metallicity tracers only probe the outer, less enriched regions. Santini et al (2010) reported that the high dust mass measured in these galaxies disagrees with the metallicity inferred from the optical metallicity diagnostics, suggesting that the optical spectral indices are likely unreliable in these dusty systems.…”
Section: Introductionmentioning
confidence: 90%
“…Herschel is also probing the coldest phases of dust in high-z galaxies. Santini et al (2010) recently found that the dust content of their high-z submillimeter galaxies appears to be far higher than that expected from their metallicity, probably revealing different dust properties or dust growth mechanism in those environments. We caution the accuracy of dust masses estimates made without rest-frame submm observations.…”
Section: Conditions For Submm Excessmentioning
confidence: 97%